A Surprising Outcome of a Patient with Psychosis: Progressive Emphysema Associated with Pneumorrhachis - Emine Polat; Halise Akça; Nilden Tuygun; Hasibe Gökçe Çınar; Can Demir Karacan (Galenos Yayinevi, 2019)
Air can be detected in various anatomical regions during the course of several diseases. This accumulation of air is often seen as pneumothorax and subcutaneous emphysema. Rarely extraordinary regions such as skull base and spinal region can be involved. In the majority of the patients, it is caused by trauma, iatrogenic factors and Valsalva maneuver. Supportive treatment is generally sufficient. A 14-year-old boy with psychosis who developed extensive air in the scull base, the neck, the orbita, mediastinum, abdomen, retroperitoneum, spinal canal, scrotum and head of the femur was presented. In the course of psychiatric disorders, in the case of excessive shouting and self-harm as a result of squeezing the throat, beside subcutaneous emphysema, air existing in the various anatomical regions of the body should be kept in mind.